State Theology and Political Populism? A Kairos Critique of Religious Populism in South Africa. - Forster, Dion A (Journal of Church & State)
The article focuses on critical theological conversation on religious populism and its role in contemporary South African politics and characterize religious populism in the South African social and political context. It mentions role of religion and religious leaders in South Africa's history. It also mentions South Africa's most prominent contemporary mainline Christian denominations the Methodist Church of Southern Africa (MCSA).